NSCA's essentials of training special populations - Jacobs, Patrick L. 1955-; National Strength & Conditioning Association (U.S.) (Champaign, IL Human Kinetics, 2018)
This volume helps exercise professionals design customised programmes for clients with special conditions and needs. It's also the ideal resource for those seeking to become a National Strength and Conditioning Association (NSCA) Certified Special Population Specialist (CSPS). The text discusses the benefits of exercise for clients with special conditions and the exercise-related challenges they often face. Also, there are details on the importance of safe and effective health and fitness assessments for these clients. Throughout the text, there are a number of learning aids. These come in the form of chapter objectives, study questions, key terms and extra recommended reading.
Rationale and considerations for training special populations / Patrick L. Jacobs -- Health appraisal and fitness assessments / John F. Graham, Malcolm T. Whitehead -- Musculoskeletal conditions and disorders / Carwyn Sharp -- Metabolic conditions and disorders / Thomas P. LaFontaine, Jeffrey L Roitman, Paul Sorace -- Pulmonary conditions and disorders / Kenneth W. Rundell, Pnina Weis -- Cardiovascular conditions and disorders / Ann Marie Swank, Carwyn Sharp -- Immunological and hematological conditions and disorders / Jay Dawes, Benjamin Reuter, Don Melrose, Misty Kesterson -- Neuromuscular conditions and disorders / Patrick L. Jacobs, Stephanie M. Svoboda, Anna Lepeley -- Cognitive conditions and disorders / William J. Kraemer, Brett A. Comstock, James E. Clark -- Cancer / Alejandro Ferrer San Juan, Steven J. Fleck, Alejandro Lucía Mulas -- Children and adolescents / Avery D. Faigenbaum -- Older adults / Wayne L. Westcott -- Female considerations / Jill A. Bush-Wallace.
Includes bibliographical references (pages 429-503) and index.
Keywords: Physical fitness -- Physiological aspects; Exercise -- Physiological aspects; Cognition -- Effect of exercise on; Exercise therapy; Physical fitness for people with disabilities; Physical education and training